Synthetic poly(2‐acrylamido‐2‐methylpropanesulfonic acid) gel induces chondrogenic differentiation of ATDC5 cells via a novel protein reservoir function. Issue 3 (27th July 2020) - Semba, Shingo; Kitamura, Nobuto; Tsuda, Masumi; Goto, Keiko; Kurono, Sadamu; Ohmiya, Yoshihiro; Kurokawa, Takayuki; Gong, Jian Ping; Yasuda, Kazunori; Tanaka, Shinya
Abstract: We previously demonstrated that a synthetic negatively charged poly(2‐acrylamido‐2‐methylpropanesulfonic acid) (PAMPS) gel induced chondrogenic differentiation of ATDC5 cells. In this study, we clarified the underlying molecular mechanism, in particular, focusing on the events that occurred at the interface between the gel and the cells. Gene expression profiling revealed that the expression of extracellular components was enhanced in the ATDC5 cells that were cultured on the PAMPS gel, suggesting that extracellular proteins secreted from the ATDC5 cells might be adsorbed in the PAMPS gel, thereby contributing to the induction of chondrogenic differentiation. Therefore, we created "Treated‐PAMPS gel, " which adsorbed various proteins secreted from the cultured ATDC5 cells during 7 days. Proteomic analysis identified 27 proteins, including extracellular matrix proteins such as Types I, III, and V collagens and thrombospondin (THBS) in the Treated‐PAMPS gel. The Treated‐PAMPS gel preferentially induced expression of chondrogenic markers, namely, aggrecan and Type II collagen, in the ATDC5 cells compared with the untreated PAMPS gel. Addition of recombinant THBS1 to the ATDC5 cells significantly enhanced the PAMPS‐induced chondrogenic differentiation, whereas knockdown of THBS1 completely abolished this response. In conclusion, we demonstrated that the PAMPS gel has the potential to induce chondrogenic differentiation through novel reservoir functions, and the adsorbed THBS plays a significant role in the induction.